PENGARUH STORY TELLING TERHADAP PERKEMBANGAN BAHASA PADA ANAK USIA PRA SEKOLAH (TK B) DI TK PGRI 02 TANJUNG JATI KECAMATAN KAMAL KABUPATEN BANGKALAN - LESTARI, INDAH; INDATUL L, SITI (JURNAL KEPERAWATAN BINA SEHAT, 2014)
Delays of language skills are still experienced by many pre-school children, especially on class B. Lack of stimulus especially the use of language cause the destruction of the connection and branching of cortical regions of the brain, so that children will experience delays of language skills. This research aims to prove the influence of storytelling on the development of language in pre-school age children (kindergarten B) in TK PGRI 02 Tanjung Jati Kamal Sub District Bangkalan District. Research design is comparative analytical study with pre-experimental approach and pre-post test in one group type. Population was all pre-school age children (kindergarten B) as many as 48 children and sample as many as 39 children which is taken using purposive sampling. The independent variable is the implementation of storytelling and the dependent variable is language development of preschool-age children. Data were collected using a check list, then processed and analyzed using the Wilcoxon Sign Rank Test. The results showed before the implementation of storytelling, the majority of respondents had a suspected language development as many as 24 respondents (61,5%) and after the implementation of storytelling, most have suspected language development as many as 22 respondents (56,4%). Wilcoxon Sign Rank Test results obtained p value (0.000) <α (0.05) = H0 is rejected, means that there is the influence of storytelling on language development in pre-school age children (kindergarten B). Story telling is a form of communication that can attract childrens attention, so it easily capture the imagination of children served the purpose of the story and process them into information of interest to replicate the activity of language. Children should like to read and actively practicing in the writing, while teachers can use storytelling as part of the curriculum and can be tested in pre-school age children on class A.Keywords: storytelling, language development, pre-school children